Marriage Legalization (Itsbat Marriage) for Unregistered Mixed Marriages (Study of Decision Number: 62/Pdt.P/2016/PA.JB) - Indah Umami; Endang Heriyani (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Article 2 (2) of Law No. 1 of 1974 on Marriage stipulates that every marriage must be registered in accordance with applicable laws and regulations. For Muslims, marriage registration takes place at the KUA. However, in reality, many citizens still enter into unregistered marriages (siri), which are not officially recorded due to difficulties in meeting document requirements, particularly for Indonesian citizens (WNI) marrying foreign nationals (WNA). Unregistered marriages have detrimental effects, particularly on the wife and children. This study is a normative legal research that examines the legal system as its subject. The objective of this study is to determine the legal considerations of the judge at the Jakarta Barat Religious Court in granting the itsbat marriage ruling for an unregistered mixed-marriage in Decision No. 62/Pdt.P/2016/PA.JB. The conclusion of the study is that the legal reasoning of the judge of the West Jakarta Religious Court in granting the petition for the recognition of marriage in Decision No. 62/Pdt.P/2016/PA. JB, the judge referred to Article 14 of the Compilation of Islamic Law, which governs the pillars of  marriage, and the fiqh doctrine  in the book Bughyatul Mustarsyidin, page 298, regarding marriage witnesses, and the book Tuhfah, Volume IV, page 133, regarding the acknowledgment of marriage by a bride who has reached puberty.  The judge determined that the essential elements and conditions for conducting a marriage under Islamic Law had been fulfilled. Thus, the judge’s decision to grant the petition for marriage validation was in accordance with existing regulations.